A Behavioral Theory of R&D Expenditures and Innovations: Evidence from Shipbuilding - Greve, Henrich R. (Academy of Management Journal, 2003)
I base an integrated model of innovation development and launch on the behavioral theory of the firm. This model specifies that research and development expenses are increased when low performance causes ?problemistic search? and when excess resources cause ?slack search.? Innovations generated by search are launched if low performance gives managers high risk tolerance. Using data from shipbuilding firms, I show that high performance reduces R&D intensity and innovation launches, and high slack increases R&D intensity, as predicted.